The Effectiveness of Problem-Based Flipped Classroom Model in Improving Chemistry Learning Outcomes of Buffer Solution - Nurul Lestari Musva; Maria Erna; Abdullah Abdullah (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The concept of buffer solutions is ubiquitous in everyday life, encompassing macroscopic, symbolic, and microscopic representations. Effective learning of these concepts requires students to understand the subject matter, analyze it, and apply their knowledge to real-life situations. This study aimed to assess the impact of problem-based learning in a flipped classroom model on the learning outcomes of 11th-grade science students studying buffer solutions at SMAN 12 Pekanbaru. The study employed a quasi-experimental design with a pretest-posttest control group. The sample consisted of two groups of 11th-grade science students: Group 3 served as the experimental group and Group 4 as the control group. Data was collected through a test and analyzed using t-test in SPSS 22. The results revealed that the problem-based learning approach in the flipped classroom model effectively improved the learning outcomes of 11th-grade science students studying buffer solutions at SMAN 12 Pekanbaru. The experimental group showed an average improvement of 7.394 over the control group, with a significant (α) t-value of 0.013.